The Effect of Training on Spirituality Therapy on Reduction of Marital Along with Drug Control in Fidelity Crisis Betrayed in Isfahan City, Iran - Mohsen Saeid Manesh (Journal of Global Pharma Technology, 2017)
Increasing family betrayal and the conflict is a serious threat to the society and community, because upbringing a healthy generation for today and tomorrow, who can take the responsibility of society for today and future can't be reached in a peaceful and safe environment. Hence, the need for improvement in marital interaction and diverse program has raised more than before. This study aimed the need for a training method based on spirituality therapy on reduction of marital infidelity crisis of betrayed spouses. So 60 people were chosen by simple random sampling, and were placed into two groups named test (n=30) and control (n=30). Each participant answered to three Enrich test, after Mississippi event, and questionnaire of spiritual effect on the Avants behavior, which the test group during 8 sessions of one hour and half by a group training received treatment based on spirituality. For analyzing the results, descriptive and inferential statistical techniques for data analysis, and use of the Kolmogrove-Smirnov test to verify the normal distribution of data as a prerequisite analysis of covariance were used. Statistical results of the study show that group training based on spirituality therapy on reduction of marital in fidelity crisis betrayed on P>0.05 level is meaningless, and affect only some factors including: stress, depression, spirituality, personality, financial management, religious orientation, and these changes are preserved over one month investigation